2018
DOI: 10.3389/fphy.2018.00079
|View full text |Cite
|
Sign up to set email alerts
|

A Remark on the Fractional Integral Operators and the Image Formulas of Generalized Lommel–Wright Function

Abstract: In this paper, the operators of fractional integration introduced by Marichev-Saigo-Maeda involving Appell's function F 3 (•) are applied, and several new image formulas of generalized Lommel-Wright function are established. Also, by implementing some integral transforms on the resulting formulas, few more image formulas have been presented. We can conclude that all derived results in our work generalize numerous well-known results and are capable of yielding a number of applications in the theory of special f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 13 publications
(12 reference statements)
2
23
0
Order By: Relevance
“…Then, it is a turn to consider the nature of the generalized Lommel-Wright function treated in the commented paper [1]. There, we find its definition (1.1) and also a representation as a generalized Wright hypergeometric function (1.2), namely:…”
Section: The Case In the Commented Papermentioning
confidence: 89%
See 3 more Smart Citations
“…Then, it is a turn to consider the nature of the generalized Lommel-Wright function treated in the commented paper [1]. There, we find its definition (1.1) and also a representation as a generalized Wright hypergeometric function (1.2), namely:…”
Section: The Case In the Commented Papermentioning
confidence: 89%
“…The commented paper [1] is one example of a long list of recently published works devoted to evaluation of the images of classes of special functions under the classical operators of fractional order integration and differentiation and their various generalizations. The used procedures are usually same standard ones [interchanging the order of integration and summation, as in (2.3), [1]]. And in many cases the resulting expressions are complicated and involve special functions different in kind from the originals.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Jain ([17], p. 1-11) introduced a novel and powerful numerical scheme and implemented to different fractional order differential equations. Some other interesting and significant studies on fractional derivatives can be found in [18][19][20][21][22][23][24][25][26] and the references therein.…”
Section: Introductionmentioning
confidence: 99%